Application of Technology and Fertilizer Management on Oil Palm Plants in Kinali Village: Penerapan Teknologi dan Manajemen Pemupukan Pada Tanaman Kelapa Sawit di Desa Kinali - Wahyudi, Wahyudi; Ezward, Chairil; Desta Andriani; Seprido, Seprido; A.Haitami; Elfi Indrawanis; Tri Nopsagiarti; Gusti Marlina; Budi Santoso (Universitas Lancang Kuning, 2025)
Oil palm planting should pay attention to technology and fertilization management. The hope in cultivating oil palm plants is the results/production of the fruit. The community in Kinali Village has begun to convert rubber plantations into oil palm plantations. However, some people still do not know the importance of understanding and implementing fertilization properly. The method of community service activities is to start identifying problems through dialogue which is continued with extension and training activities. In order to measure the level of satisfaction with the activities carried out, a questionnaire was distributed. The results of this activity showed that the community was very satisfied (83,33 %) with the extension and training provided. The importance of this activity is because it increases knowledge, changes mindsets and changes the treatment of community oil palm plants. So that it can increase community income.